Analysis of Dense Metals Accumulation in Shikaripara Stone Mines - Gorai, Gopinath; Mandal, Nirajan Kumar (Makara Journal of Science, 2024)
This study aimed to measure the amount of dangerous substances in the cultivated area of the Shikaripara stone mines in Jharkhand, India, which are well known for their stone quarrying. Sixteen soil samples were collected at varying dis-tances from the Shikaripara stone mines in the Dumka District of Jharkhand. The metals found in these samples in-clude Pb, As, Zn, Mn, Cd, Cu, Fg, and Fe. The combined amount of the elements was calculated by inductively coupled plasma mass spectrometry. Enrichment factor, accumulation index, contamination factor, pollution load index (PLI), Nemerow index, and ecological risk index (RI) were employed to assess the level of concentration. Nearly all of the soil samples had lower metal concentrations than normal shale. Among the anthropogenic contributions, principal compo-nent analysis identified three components accounting for 82.6% of the data variability. PLI, RI, and index Nemerow were calculated to ascertain the effects of different toxic substances on the soils. The results revealed that 50% of the total of the areas had considerable pollution of Cu, Zn, Hg, Mn, Cd, As, Fe, and Pb. Extremely high levels of Cu, Zn, and As pollution were located in the soils used in agriculture, and these pollution levels were influenced by how close the areas were to copper mining and processing operations. This study found that the study area had a lower degree of el-emental pollution compared with other countries and places.